ANALISIS SEGMENTASI DEMOGRAFIS DAN PSIKOGRAFIS NASABAH BANK SYARIAH INDONESIA DI KOTA PALEMBANG - Effendi, Muhammad Riska Maulana (Jurnal Media Ekonomi (JURMEK), 2025)
This study was conducted to analyze the influence of customer demographic and psychographic segmentation on service selection at Bank Syariah Indonesia in Palembang City. The analysis used a non-probability sampling method, involving one hundred customers, whose data was collected through a questionnaire over a one-month period. The raw data was processed using regression and correlation approaches to determine the relationship and influence of these two segmentations on Bank Syariah Indonesia's services in Palembang City. The results showed a regression coefficient of 0.479 for demographic segmentation and 0.265 for psychographic segmentation, with a correlation of 0.832 and a coefficient of determination of 0.693.